Effects of rainfall distribution towards oil palm yield at Ladang Bukit Kelompok, Kota Tinggi, Johor / Ahmad Syahidan Roslan - Roslan, Ahmad Syahidan (Faculty of Plantation and Agrotechnology, 2017)
Rainfall is one the climate change that has potential to influence the palm oil production. The intensity of rainfall is importance in providing optimum condition for oil palm. This case study is stress on the effects of rainfall distribution towards oil palm yield at Ladang Bukit Kelompok that located at Kota Tinggi, Johor. The data for rainfall variations and oil palm production are collected monthly for three years which from 2013-2015. The highest rainfall for five months is choose and analyzed by using the Minitab software and Microsoft Excel application. The main objective for this case study is to understand the pattern of palm oil production relation to the one of nature scenario. The results obtained there is significant difference between rainfall distribution and palm oil yield. The conclusion is, rainfall does give major effect to the oil palm production.